195k views
3 votes
Solve: 3 + 5n = 5(n + 2) - 7 * what solution is it and please explain i need a good grade

User Bulvak
by
4.9k points

1 Answer

3 votes

Answer:

3+5n=5(n+2)-7*

We move all terms to the left:

3+5n-(5(n+2)-7*)=0

We calculate terms in parentheses: -(5(n+2)-7*), so:

5(n+2)-7*

We add all the numbers together, and all the variables

5(n+2)

We multiply parentheses

5n+10

Back to the equation:

-(5n+10)

We get rid of parentheses

5n-5n-10+3=0

We add all the numbers together, and all the variables

-7!=0

There is no solution for this equation

Explanation:

User Raanan Avidor
by
4.7k points